Factors influencing turnover intention of employees at Gloco Malaysia Sdn. Bhd. / Nurmazidah Onn - Onn, Nurmazidah (Faculty of Business and Management, 2018)
Employee is a valuable asset which the one who brings output to organization. Nowadays, it becomes challenging to organization to retain existing employees due to turnover. Turnover intention of employees is influencing to actual rate of turnover in organization. Many researchers have found that there are many factors contributing to turnover intention which focuses on employees working at private company. However, there is limited of study focuses on employee in Information and Technology (IT) Industry whereby it is one of huge industry in Malaysia. Therefore, the main objective of this study is to investigate the relationship of the factors influencing employee turnover intention at Gloco Malaysia Sdn. Bhd which is one of IT Healthcare companies in Malaysia. This research however will mainly focus on the four factors that influence employee turnover intention which are job satisfaction, role stress, leader-member exchange and human resources management practices. The data collected in this study involved 60 of total employees are the population in this study and Statistical Analysis System has been used in our research. A Cronbach’s Alpha has been used to test the reliability of the independent variable and also dependent variable. Moreover, the Pearson Correlation Coefficient and Multiple Linear Regression Analysis have been used in this research in order to determine the relationship between four independent variables and dependent variable. By the end of this study, it was concluded that the three independent variables which are job satisfaction, role stress and leader-member exchange are important and influential to turnover intention.